Evaluation of the antifungal effect of saliva officinalis extract in vitro - Mustafa Al-Ahmad, Basma Ezzat; Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Quta, Lolita; Shaban , Sama (2015)
Background/Objectives: Saliva officinalis (sage) is a natural product that has been given more consideration these days because of its beneficial health effect. There are a lot of active Compounds from S. officinalis essential oil have been shown to exhibit high antibacterial activity against Staphyloccocus aureus, Escherichia coli, and Pseudomonas aeruginosa; however, there are only few studies on its antifungal effects. The aim of this research is to investigate antifungal ability of different types of Saliva officinalis extract in vitro, and to compare their potency. Materials and Method: Oil and water-based extracts of Saliva officinalis were used in this study in different concentrations, compared to Nystatin(100 units) as a positive control. Inhibitory effect of different concentrations of Saliva officinalis extract on candida albicans was studied under in vitro conditions. The antifungal activity of the extract was measured by percent radial growth inhibition. 500 ppm of the extract was found to have a high inhibitory effect on candida albicance growth. Results & Discussion: Assessment of conidial growth by using different concentrations showed that the oil extract exhibited 90 % inhibition of candidal growth at 500 ppm, comparing to the water extract which exhibited only 40% inhibition of the growth in the same concentration ,according to this study the fungicidal concentrations of S. officinalis oil is 500 ppm . It was found that Sage oil was more than the water extract. Conclusion: this study shows that oil extract has high antifungal activity comparing to the water extract .Based upon the present study it could be concluded that Saliva officinalis oil extract might be promising as a mouth wash in reducing the fungal growth in oral cavity and the incidence of side effect that may occur with some synthetic product.